MusykilÃ¢tul al-Mudarris fÃ® TashmÃ®mi TadrÃ®s al-Lughah al-’Arabiyah fÃ® al-Shaffi al-TÃ¢snÃ® min Madrasati al-FalÃ¢h al-’Ã‚liyah al-IslÃ¢miyah Sumber Gayam Kadur - Taufikurrahman, Raden; Aliyah, Unayyizaturrafiatul (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2020)
This study answers two main questions, about what problems are faced by teachers in designing Arabic language learning in class 2 MA Sumber Gayam Kadur along with the solution. The researcher used qualitative methods and analytical descriptive studies. Then, the data sources for this study included Arabic language teachers, a number of class 2 students, and the school principal of MA Sumber Gayam Kadur. All data presented in this study came from structured and unstructured interviews, observations, and documentation. This research proves that the problems faced by teachers include the selection of the best methods that are most suitable for students who are not homogeneous, time management that must be managed properly, and problems related to the application of learning steps that are appropriate to the classroom conditions. From all of these problems, the researcher can conclude the solution by presenting at least 2 experts to update the curriculum every year, encouraging teachers to be active in training organized by the local government and the Foundation’s full support in improving the quality of teachers.